Renewable levulinic acid production catalyzed by iron modified by hy zeolite and functionalized ionic liquid - Nur Aainaa Syahirah Ramli, 1988- , author; Nor Aishah Saidina Amin, 1963- , supervisor; Fakulti Kejuruteraan Kimia (2015)
Thesis (Ph.D (Kejuruteraan Kimia)) - Universiti Teknologi Malaysia, 2015